Tuberculosis control programme from NTCP to RNTCP to NTEP - Bhardwaj, Ashok Kumar (Indian Journal of Community Health, 2020)
India, the highest TB burden country in the world, is having an estimated incidence of 26.9 lakh cases in 2019 (WHO). The year 2019 marks another milestone year for TB surveillance effort in India, with a record high notification of 24 lakhs cases; an increase of over 12% as compared to 2018. Of the 24 lakhs TB cases,(1) 21.6 lakhs were incident TB cases (New and Relapse/ Recurrent). This amount to an incident notification rate of approximately 159 cases/lakh against the estimated incidence rate of 199 cases/ lakh population; thus, closing the gap between the estimated and notified incident cases to just 40 Cases per lakh population, or an approximate of 5.4 lakh missing cases across India.